Fenomena Fear Of Missing Out (FoMO) di Kalangan Generasi Z Kota Bengkulu - Leoni Okta Verina; Panji Suminar; Ika Pasca Himawati (LPPM Institut Pendidikan Nusantara Global, 2026)
Fear Of Missing Out(FoMO) is a social phenomenon that reflects an individual's concern about the possibility of being left behind by various information, activities, or trends developing in their environment. The aim of this study is to analyze the factors that influence this.fear of missing out(FoMO) among Generation Z in Bengkulu City. The research approach used was quantitative, with data collected through a questionnaire (Google Form) distributed via social media. The research sample consisted of 385 respondents aged 13-29 who actively use TikTok, Instagram, Facebook, and WhatsApp. The sample was determined using the Krejcie and Morgan formula. Data analysis was conducted through multiple regression, T-test, F-test, and coefficient of determination (R2).2). The results of the study showed that simultaneously, family, peer, social media use, age, and gender factors had a significant effect on FoMO with a calculated F value > F table (208.642 > 2.24) and a significance of 0.001. Partially, family, peer, and social media use factors had a significant effect, while age and gender did not have a significant effect. The coefficient of determination test showed that 73.4% of the variation in FoMO could be explained by the research variables, while 26.6% was influenced by other factors outside the model. This finding confirms that the social environment and intensity of social media use are dominant factors in the formation of FoMO in Generation Z, especially in Bengkulu City. Therefore, digital literacy and social support from family and peers are needed to reduce the negative impacts caused by dependence on social media.